2019
DOI: 10.1002/jcp.28479
|View full text |Cite
|
Sign up to set email alerts
|

Loss of MCL1 function sensitizes the MDA‐MB‐231 breast cancer cells to rh‐TRAIL by increasing DR4 levels

Abstract: Triple‐negative breast cancer (TNBC) is a form of BC characterized by high aggressiveness and therapy resistance probably determined by cancer stem cells. MCL1 is an antiapoptotic Bcl‐2 family member that could limit the efficacy of anticancer agents as recombinant human tumor necrosis factor related apoptosis‐inducing ligand (rh‐TRAIL). Here, we investigated MCL1 expression in TNBC tissues and cells. We found MCL1 differentially expressed (upregulated or downregulated) in TNBC tissues. Furthermore, in compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Alternative approaches that induce Mcl1 proteasomal degradation (by GDC-094 treatments, for example), have also been effective in overcoming resistance, thus allowing ABT-737 to have greater effects against BC cells [ 346 ] and lung cancer (LC) cells [ 106 ]. Similar effects have also been reported for Mcl1 inhibition and TRAIL co-stimulation of BC cells [ 338 ]. Conversely, stabilization of Mcl1 protein by BAG3 and survival of BC and PC cells under ABT-737 stimulatory conditions has also been reported [ 105 ], highlighting a central but indirect and positive regulatory mechanism for the Mcl1 protein as a therapeutic resistance factor.…”
Section: Main Textsupporting
confidence: 86%
“…Alternative approaches that induce Mcl1 proteasomal degradation (by GDC-094 treatments, for example), have also been effective in overcoming resistance, thus allowing ABT-737 to have greater effects against BC cells [ 346 ] and lung cancer (LC) cells [ 106 ]. Similar effects have also been reported for Mcl1 inhibition and TRAIL co-stimulation of BC cells [ 338 ]. Conversely, stabilization of Mcl1 protein by BAG3 and survival of BC and PC cells under ABT-737 stimulatory conditions has also been reported [ 105 ], highlighting a central but indirect and positive regulatory mechanism for the Mcl1 protein as a therapeutic resistance factor.…”
Section: Main Textsupporting
confidence: 86%
“…One way MCL1 contributes to AML relapse is by promoting resistance to certain treatments. For example, MCL1 has been found to be differentially expressed in triple-negative breast cancer (TNBC) tissues and cells, potentially limiting the efficacy of anticancer agents like recombinant human tumor necrosis factor-related apoptosis-inducing ligand (rh-TRAIL) [35]. In AML, MCL1 downregulation has been observed when CDK7 inhibitor THZ1 is combined with azacitidine (AZA), resulting in synergistic antileukemic effects in AML cell lines and primary cells [36].…”
Section: Discussionmentioning
confidence: 99%
“…Treatments targeting MCL1 could be an effective strategy to overcome rh-TRAIL resistance in Triple Negative Breast Cancer (TNBC). 19 Other studies also identified the essential role of Mcl-1 in promoting chemoresistance and showed that Mcl-1 could be a promising target for the treatment of ovarian cancer. 18,20 MicroRNAs (miRNAs) are small noncoding RNAs (21-25 nucleotides) that act post-transcriptionally to suppress gene expression.…”
Section: Discussionmentioning
confidence: 99%